Handbook of industrial, work and organizational psychology. Vol. 1, Personnel psychology - Anderson, Neil, 1961-; Sage eBooks (London : SAGE, 2001)
The first volume of the Handbook of Industrial, Work and Organizational Psychology focuses on the theories, techniques & methods used by industrial psychologists. The second concerns research findings on a range of work-related topics.
Specialized.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Psychology, Industrial; Work -- Psychological aspects; Organization -- Psychological aspects; Electronic books